Facial burn injury treatment: A review of facial mask fabrication using rapid prototyping technology - Fozi, Aiman; Salleh, Mohamed Najib; Ismail, Khairul Azwan (2014)
This article gives an overview of the fabrication process of the facial mask that used in pressure therapy treatment for facial burn injury.The use of the different processes either conventional or 3D scanning method is discussed within this paper.The objective of this paper is to propose a new method of fabricating the facial mask using reverse engineering method and vacuum casting for producing a mask from elastic material, especially medical grade silicone. Vacuum casting was known for the capability of replicate the details on the master part and the ease of fabrication process.Analytical study of the face mask will be conducted using CAE software to simulate the pressure exerted by the designated mask.